Pengaruh Metode Belajar Terhadap Hasrat Belajar dan Hasil Belajar Senam Lantai Siswa Sekolah Dasar - Septiawan, Dedi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
This test intends to show the quality of students' learning desires greatly affects students' floor exercise learning outcomes. This test is a type of true experiment that uses pre-test and post-test testing. The data sample used in this study amounted to 30 students from classes V and VI who were randomly selected. Then the data was analyzed using descriptive analysis and analysis of variance (ANOVA) with a significance level of 0.05. The results showed: 1) The learning outcomes of floor gymnastics of students who use the Jigsaw method are higher than students who use conventional methods with an average learning outcome of 88.01: 80,99, 2) Qualitative students in interacting during learning greatly affect the quality of student interest in learning and also student learning outcomes, and 3) The quality of learning interest can also be a measure of student learning outcomes for a lesson. Research conclusions: 1) Compared to the learning outcomes of conventional floor exercise method, the learning outcomes of jigsaw method are higher, 2) The quality of interaction and students' learning desire in learning floor gymnastics has a major effect on students' floor gymnastics learning outcomes, and 3) The quality of students' learning desire is closely related to students' learning outcomes.